PENELITIAN TENTANG KENDALA DALAM PENGGUNAAN TEKNOLOGI PENDIDIKAN DAN TINGKAT PERSIAPAN DIGITAL DI SEKOLAH MENENGAH INDONESIA: PENELITIAN DI SMA NEGERI 5 PADANG - Rahmadesi, Nurjanah; Jasrial; Zen, Zelhendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of education through digital means has notably propelled secondary schools in Indonesia to adopt digital tools in their teaching and learning frameworks. Nevertheless, the application of educational technology continues to face various obstacles that could impede the success of learning that is based on digital platforms. This research intends to identify the challenges in the application of educational technology and evaluate the extent of digital readiness among school stakeholders at SMA Negeri 5 Padang. A quantitative descriptive methodology was utilized, employing a survey approach. Information was gathered via questionnaires given to teachers and students chosen through purposive sampling. The research tool was crafted taking into account the aspects of Technology Readiness, digital literacy, technological infrastructure, and institutional support. Data were analyzed using descriptive statistics alongside a digital readiness index. The results show that SMA Negeri 5 Padang possesses a high level of digital readiness, reflected by an average index score of 3.84 out of five. Among the evaluated aspects, technological optimism and adaptability received the highest ratings, while challenges remain regarding infrastructure availability and the quality of internet connectivity. Key obstacles identified consist of inconsistent internet access, varying levels of digital skills among users, lack of ongoing training in educational technology, and ineffective use of digital learning resources. These findings imply that while individual capability to embrace technology is relatively strong, there is still a need to enhance the school's digital framework through upgraded infrastructure, improved digital skills for teachers, and long-term policy backing. This research offers practical insights for the formulation of digital transformation strategies within Indonesian secondary education to create more effective, inclusive, and flexible learning environments in light of technological evolution. The findings align with earlier studies that highlight the importance of digital readiness, technological proficiency, and institutional support as crucial factors for the successful integration of educational technology in secondary institutions.